Retrograde Ureteroscopy in the Management of Distal Ureteric Stones: A Retrospective Analysis of Outcome and Complications - Akpayak, Idorenyin Cletus (Ann Afr Med, 2020)
BACKGROUND: Urinary stones affect 8%–15% of the world population. In Nigeria, contemporary reports have shown that the incidence of urinary stones is rising. The distal ureter has been described as the most common location of ureteric stones. This study seeks to review our experience in the ureteroscopic management of distal ureteric stones with a view to appraising the stone clearance rate and the complications seen in our patients. PATIENTS AND METHODS: This descriptive study reviewed the record of 21 patients, who had semirigid ureteroscopy and pneumatic lithotripsy for distal ureteric stone between October 2015 and September 2018. All patients had computed tomography urography preoperatively to locate the stone. Data on patients' demographics, indication for the surgery, location and size of stone, preoperative double-J (DJ) placement, postoperative DJ stent placement, intraoperative and postoperative complications, and status of stone clearance were retrieved and subjected to statistical analysis. RESULTS: The mean age of the patients was 37.95 ± 11.09 (range, 21–67) years. The mean stone size was 8.06 ± 2.87 mm with a range of 4.8 mm–15.0 mm. Out of the 21 patients, 20 (95.2%) had the procedure for recurrent ureteric colic and 1 (48%) was for hematuria. Four (19.0%) patients had DJ stent preoperatively, whereas 17 (81.0%) patients did not have. Fourteen (66.7%) patients had intraoperative ureteric dilatation. Postoperative DJ stent was placed in 17 (81.0%) patients, whereas 4 (19.0%) patients did not have. Three (14.3%) patients had mucosal flap, 6 (14.3%) had mucosal abrasion, 2 (9.5%) had bleeding, 1 (4.8%) patient had transient hematuria postoperatively, and 2 (9.5%) patients had urinary tract infection. Nineteen (90.5%) patients had complete clearance in a single surgery. Two (9.5%) patients had symptomatic residual fragments that required repeat ureteroscopy. CONCLUSION: Our study has shown that ureteroscopy is a useful and safe technique in the removal of stones in distal ureter.